Cartagena de Indias Declaration. XIV Summit of Heads of State and Government - de Río, Grupo (2016)
The Heads of State and Government, in the city of Cartagena de Indias, on the occasion of the XIV Summit of Heads of State and Government of the permanent consultation and consultation mechanism of the Rio Group, adopted the "Declaration of Cartagena: a commitment for the Millennium "on June 14, 2000.